Physiological Activity of Salmonella spp. Bacteria After Lyophilization and Rehydration - Romanko , Maryna; Ushkalov, Valerii; Paliy , Anatoliy; Paliy , Andrii; Petrov , Roman; Livoshchenko , Lyudmila; Livoshchenko , Yevheniia (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(2):158–163